Dielectric and electrical properties of Cr substituted Mg ferrites (Journal of Bangladesh Academy of Sciences, 2015)
The spinel ferrites MgCrxFe2-xO4 (0.0 ? × ?1.0) were prepared through the solid state reaction using conventional ceramic method at 1300°C in air. The homogeneous phase of the ferrite samples was observed from the X-ray diffraction study. Lattice parameter of the samples was found to decrease with increasing Cr concentration in the system obeying Vegards law. The ac electrical resistivity, measured as a function of temperature, decreases with the increase of temperature indicating the semiconducting nature of all the samples. The activation energies were calculated and found to decrease with increasing Cr content. The lower activation energies are associated with higher electrical conductivity. With the increase of temperature, dielectric constant (e`) and dielectric loss tangent are observed to be increased; while with the increase of frequency, dielectric constant (e`) and dielectric loss tangent decrease for all the samples.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 1-12, 2015